Teleakses Sistem Informasi Alumni STMIK Handayani Makassar Berbasis SMS - Najirah Umar (STMIK KHARISMA Makassar, 2015)
This study aims to make it easier for alumni to obtain and provide job vacancy information via SMS, utilize a data port cable (serial COM port) as an interface between a PC and HP, and design an SMS application program to input, edit or ask for job information, then a service is designed information for alumni to make it easier to get job information.With this service system, alumni can get job vacancies information without having to go to campus, simply by using the SMS service on the cellphone, the system will automatically answer or respond to requests from clients / alumni anytime and anywhere.